The structure of human GCN2 reveals a parallel, back-to-back kinase dimer with a plastic DFG activation loop motif. Issue 1 (17th January 2020) - Maia de Oliveira, Taiana; Korboukh, Victoria; Caswell, Sarah; Winter Holt, Jon J.; Lamb, Michelle; Hird, Alexander W.; Overman, Ross
Abstract : When activated by amino acid starvation, the stress sensing protein kinase GCN2 phosphorylates the eukaryotic initiation factor 2 alpha, inhibiting translation to conserve energy and facilitate cell survival. Amino acid starvation, particularly of tryptophan and arginine, affects immune tolerance by suppressing differentiation and proliferation of T-cells via activation of GCN2 kinase. In addition, the GCN2 pathway mediates cancer survival directly within the context of metabolic stress. Here, we report the first crystal structures of the human GCN2 kinase domain (KD) in complex with two inhibitors of different size, shape, and chemical scaffold. Three novel activation loop conformations representative of different activation states of the kinase are described. In addition, a novel dimerization organization for GCN2 is observed. This arrangement is consistent with the hypothesis that the GCN2 KD forms an antiparallel inactive dimer until uncharged tRNA binds to it and triggers conformational changes that shift the equilibrium to the active parallel dimer.